Consensus statements for the establishment of medical intensive care in low-resource settings: international study using modified Delphi methodology - Kovačević, Pedja; Vidovic, Jadranka; Tomic, Boris; Mallat, Jihad; Hssain, Ali Ait; Rotimi, Muyiwa; Akindele, Owoniya Temitope; Doi, Kent; Mishra, Rajesh; Meyer, Franz Joachim; Palibrk, Ivan; Skrbic, Ranko; et al. (Critical care, 2024)
The inadequacy of intensive care medicine in low-resource settings (LRS) has become significantly more visible after the COVID-19 pandemic. Recommendations for establishing medical critical care are scarce and rarely include expert clinicians from LRS.